SWOT Analysis for SD Facilities and Infrastructure Policy - Mifthahul Jannah; Rizki Ananda; Widia Nisari; Annisya Husnul (Universitas Muhammadiyah Enrekang, 2023)
Technology is a form that is always related to Education. The form of technology affects every step of education. Schools that have educational steps side by side with technology by completing facilities and infrastructure. So that the purpose of the study is to analyze the grain of facilities and infrastructure in elementary schools and through SWOT (strengths, weaknesses, threats, and opportunities) in the management of facilities and infrastructure. This type of research is Qualitative description. This research consists of a SWOT analysis that examines the importance of facilities and infrastructure, and the management of facilities and infrastructure. Infrastructure facilities are always associated with supporting the educational success of a student. therefore we must know the facilities and infrastructure that support the success of education. Through education, infrastructure can be formed and support the success of education. Good infrastructure also makes students enthusiastic in the learning process, as well as comfortable in demanding knowledge. The conclusion of this study is in the form of facilities and infrastructure policies, SWOT analysis in elementary school infrastructure, planning, management of facilities and infrastructure